DAMPAK PENGEMBANGAN PARIWISATA TERHADAP KONDISI LINGKUNGAN PESISIR DAN STRATEGI PENGEMBANGANNYA DI PANTAI YEH GANGGA, KABUPATEN TABANAN - Pradnyani, Gusti Ayu Manik; Sudiana Mahendra, Made; Diara, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 17 No 2 (2023), 2023)
The Tabanan Regency Government has established Yeh Gangga Beach as one of the tourist attractions. Tourism development will certainly have an impact on the physical, social and economic environment of the local community as well as for the tourism area itself. So it is necessary to conduct research on how much tourism impact the physical environment and the social and economic communities on the coast of Yeh Gangga Beach. The method used in this research is mixed, using two types of data, namely quantitative data related to population data and questionnaire results, as well as qualitative data through observation and interview methods related to data on the physical environment and socio-economic conditions of tourism. The analysis method to formulate alternative strategies that can be applied in the development of Yeh Gangga Beach is done by SWOT analysis. Tourism development is in line with the construction of tourism support facilities. There are changes in the coastline in the form of accretion caused by the construction of trails and there are two river mouths large enough to cause sedimentation. The river water quality is still classified as good and has a parameter value that is not much different because it has almost the same water activity. Tourism development on Yeh Gangga Beach has positively impacted the local community’s economy and income, with changes in livelihoods and income. The calculation results of the strength factor obtained a score value of 1.96 and a weakness value score of 0.91 with a score difference of +1.04. then the opportunity factor obtained a score value of 2.01 and a threat value score of 0.66 with a difference of +1.35 so that Positive-Positive (+, +) results were obtained, namely in Quadrant I. This position indicates that internal strengths and environmental conditions support tourism development so strategic recommendations are given by way of internal strengths and environmental conditions that support tourism development. This position indicates that the internal is strong and the environmental conditions support tourism development, SO the strategy recommendations are given by making the most of the strengths and opportunities possessed. Keywords: Environment, Tourism, Impact, Development Strategy